Analytical investigation of the delay system with structural matrix having eigenvalues on the unit circle - Gintarė Leonaitė; Jonas Rimas (Lietuvos Matematikos Rinkinys)
Investigation of the mutual synchronizatin system with delays, composed of n (n= 2p +1, p ∈ N) oscillators joined into a onedirectional ring, is carried out. The investigation is based on the use of eigenvectors of the matrix, which describes the structure of the internal links of the system.